How to close classic bladder exstrophy: Are subspecialty training and technique important?. Issue 5 (October 2018) - Inouye, Brian M.; Purves, J. Todd; Routh, Jonathan C.; Maruf, Mahir; Friedlander, Daniel; Jayman, John; Gearhart, John P.
Summary: Introduction: Successful primary closure is one of the main factors for achieving continence in a classic bladder exstrophy (CBE) patient. Even with contemporary management, patients still have failed primary closures. We sought to understand the role of training, surgical technique, and their impacts on outcomes of CBE closure. Materials and methods: A retrospective cohort study from the largest single-institution database of primary and re-closure CBE patients in the world was performed. Failed closure was defined as developing bladder outlet obstruction, wound dehiscence, bladder prolapse, or any need for a re-closure operation. Patient demographics and surgical factors were abstracted and analyzed. Multivariable analysis was performed to test for associations with successful exstrophy closure. Results: Data from 722 patients were analyzed. On bivariate analysis, successful closure was associated with gestational age at presentation, time of closure, location of closure, credential of surgeon performing the closure, closure type, concomitant osteotomy, and type of immobilization. Multivariable analysis, adjusting for patient comorbidity and location of closure, demonstrated increased odds of failure for closure by pediatric surgeon compared with pediatric urologist (OR 4.32, 95% CI 1.98–9.43; p  = 0.0002), closure by unknown credentialed surgeon (OR 1.86, 95% CI 1.15–2.99; p  = 0.011), Complete Primary Repair of Exstrophy (CPRE) closure compared with Modern Staged Repair of Exstrophy (OR 2.05, 95% CI 1.29–2.99; p  = 0.0024), and unknown closure type (OR 4.81, 95% CI 2.94–7.86; p  < 0.0001) (Table ). Discussion: Many factors associated with failure on bivariate analysis can be explained by these patients presenting to a center of excellence or the selection bias of this cohort stemming from a single center database that have been previously published. However, the finding on adjusted multivariable logistic regression analysis that closure by a pediatric surgeon is associated with higher odds of failure is novel. The additional finding that CPRE closure is associated with failure is most likely secondary to these patients being referred to our institution after having been closed with CPRE which falsely increases its impact on closure failure. Nevertheless, as a center with a large exstrophy volume, this study draws from a cohort that is larger than any other. Conclusion: Classic bladder exstrophy closure should be performed at a center with pediatric urologists to ensure the best chance of a successful primary closure. Table Multivariable logistic regression analysis. Outcome: failure Unadjusted odds ratio (95% CI) p -value Adjusted odds ratio (95% CI) ∗ p -value Credentials of surgeon performing closure  Pediatric urologist Reference        Adult urologist 3.50 (1.43–8.59) 0.0062 1.89 (0.70–5.10) 0.21  Pediatric surgeon 7.59 (3.77–15.29) <0.0001 4.32 (1.98–9.43) 0.0002  Unknown 1.85 (1.32–2.61) 0.0004 1.86 (1.15–2.99) 0.011 Closure type  MSRE Reference        CPRE 2.83 (1.91–4.21) <0.0001 2.05 (1.29–3.26) 0.0024  Unknown 6.06 (4.06–9.06) <0.0001 4.81 (2.94–7.86) <0.0001